Corrosion study of pipeline material for seabed sediment in tropical climate - Budiea, A M A; Yahaya, N; Noor, N M; Abdullah, A H; W Ibrahim, M H; Suratkon, A; Muthusamy, K (2020)
Corrosive environments such as marine sediments can cause corrosion to steel pipelines at any time when certain conditions are met. Seabed sediment could cause severe corrosion damage due to its corrosiveness to the pipelines buried under it. Many consequences could take place in case if there is incident in oil/gas pipelines. Successfully identifying elements of corrosion in marine sediment would enhance the future of steel structure protection and monitoring systems. This article focuses on the behaviour of corrosion rate of steel located near shore environment and the aim is to determine the effect of sediment on corrosion of steel. To investigate that, simulated near shore sediment conditions have been used where the steel coupons buried in sediments which have different characteristics. Weight loss technique has been implemented to determine the weight loss rate of the steel specimens. Based on the results of this study, metal weight loss increases as the duration of exposure to seabed sediment environment become longer. The sea sediment simulated condition has given significant levels of corrosion. Conclusively, the corrosion rate of steel in seabed sediment located in tropical region is complicated and further studies are suggested.